Sistema De Información Web Para El Mejor Control Y Acceso A Las Historias Clínicas De Los Pacientes Del Centro De Salud Jequetepeque - Pairazaman Esteves, Luis Alfredo (2017)
The present thesis work entitled “WEB INFORMATION SYSTEM FOR TO IMPROVE OF PROCESSES OF ATTENTION OF THE PATIENTS OF THE CENTER OF HEALTH JEQUETEPEQUE", it was developed in order to show that you can improve administrative management, through the development and implementation of a system under Web technology, allowing remote access to information; getting queries and reports. (Patient Records, Medical Records, Patient Consultations and treated Patient Reports, Medical Records per patient). Decreasing time information management. Specifically we used PHP code (hypertext Preprocessor) with MySQL as database manager for its development was used Rational Unified Process (RUP) for Web applications and UML modeling language with extensions for Web applications (WAE). For the development of this work has been used interviews, surveys and observations, as data collection techniques, asking open and closed questions to different respondents, which served as a source of information to determine the scope of the project. Finally, as a result of this investigation we can conclude that by the Implementation of “WEB INFORMATION SYSTEM FOR TO IMPROVE OF PROCESSES OF ATTENTION OF THE PATIENTS OF THE CENTER OF HEALTH JEQUETEPEQUE" under Web technology, is able to improve the administration.